Trials for international crimes in Asia - Sellars, Kirsten (Cambridge University Press, 2016)
"Some of the earliest rules intended to limit the conduct of hostilities can be traced back two and a half thousand years to Asia. The Chinese general Sun Tzu's The Art of War, written in the sixth century BC, is now a classic text of military strategy and tactics. But it is more than that. For alongside the discussions of attack and defence, the laying of traps and the burning of arsenals, it also explores commanders' responsibilities to both sovereigns and subordinates when engaged in warfare"--